Application of the pulley tower training complex by highly qualified athletes who complete a sports career with injuries of the musculoskeletal system - Savelyeva, V. V.; Ponomarev, G. N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the effectiveness of the use of a complex of special physical exercises on the Pulley Tower multifunctional simulator for the prevention and correction of the musculoskeletal system and spine, for highly qualified athletes who completed their sports career with injuries to the musculoskeletal system.